Penfigo foliaceo no Hospital das Clinicas da Faculdade de Medicina de Botucatu, SP - Sartori-Barraviera, Silvia Regina Catharino [UNESP]; Dillon, Neuza Lima [UNESP] (My University, 1997)
BACKGROUND - Pemphigus foliaceus is an autoimmune bullous disease that is endemic in Brazil and in other South American countries such as Paraguay, Bolivia, Peru and Colombia. OBJECTIVES - To compare the observed clinical and epidemiological data with those referred in the literature. METHOD - Retrospective study in patients with pemphigus foliaceus admitted to and treated at University Hospital of the School of Medicine of Botucatu, SP, Brazil, from 1976 to 1993, analyzing the following variables: age, sex, race, origin and onset of disease. RESULTS - From 1976 to 1993, 63 patients were treated, with an average of 3.7 cases/year. Patients within the age range of 20 to 60 years old were the most affected. Most of the patients were white, females being slightly more affected than males. The majority of male patients were rural workers. Some towns presented higher incidence of cases. Most of the patients from rural areas became sick mainly in summer and in autumn. Occurrence of similar cases was observed in blood-related family members and neighbors. CONCLUSIONS - Clinical and epidemiological data were similar to those referred in the literature.
Pemphigus foliaceus at the university hospital of the school of medicine of Botucato, SP
Keywords: Epidemiology; Pemphigus; adult; autoimmune disease; brazil; bullous skin disease; family; female; human; incidence; major clinical study; male; pemphigus foliaceus; retrospective study; rural population; seasonal variation; university hospital